(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The influence of work motivation and innovative work behavior on cadet satisfaction at the Banten Shipping Polytechnic is a quantitative study which aims to see whether motivation and innovative work behavior have an influence on cadet satisfaction. Minister of Education and Culture (Mendikbud) Nadiem Makarim requires that educational institutions implement online learning. The Banten Shipping Polytechnic must innovate in learning in line with the Minister who requires online learning, so that the Banten Shipping Polytechnic also innovates in the online learning process. This research measures whether work motivation and online learning innovation have an influence on student satisfaction/ cadet.